The Ambiguity of Norms in Legal Protection for Advocates and the Problem of the Limits of Good Faith in the Criminal Justice System - Arih Wira Suranta; Indah Kusuma Wardhani (Pelopor Publikasi Akademika, 2026)
Legal protection for advocates is a fundamental prerequisite for the realization of fair trials, particularly in ensuring the independence of the defense function within the criminal justice system. The regulation of advocate immunity rights in Article 149 paragraph (2) of Law Number 20 of 2025 concerning the Criminal Procedure Code normatively guarantees that advocates cannot be prosecuted criminally or civilly in the exercise of their profession, but this protection is limited by the phrase